On the peculiarities of phase developments involving Zn2 +-doped ZrO2 system. (September 2017) - Kumar, Kundan; Jaroń, Tomasz; Chowdhury, Anirban
Abstract: ZnO-stabilized (8%) ZrO2 system appeared cubic in normal X-ray diffraction (at 500 °C) but Rietveld analyses confirmed equiproportionate ( 1:1) cubic and tetragonal phase. At 650 °C, the cubic to tetragonal phase ratio changed to 1:2 with the appearance of monoclinic phase (8 wt%). Kinetic studies with thermogravimetry data and other structural characterizations established the importance of the stabilizing cation (Zn 2 + ) for the ZrO2 matrix and confirmed that the conversion of the stabilized cubic/tetragonal phase to monoclinic ZrO2 is dependent pivotally on process kinetics (rate of heat supply), thermodynamics (absolute final temperature) and the presence/lack of oxygen in the ambience. Graphical abstract: